Alexa Archuleta: capstone - Archuleta, Alexa, artist (Colorado State University. Libraries, 2025)
The artist's statement: Since I was child, I knew that I wanted to communicate through creativity. I’m interested in many different mediums, with many roots in photography. Eventually, I found myself drawn to pursuing graphic design. I found this medium would allow me to grow rather quickly due to my previous understanding with the Adobe Suite for all of my photography, and these two mediums often go hand-in-hand. I am also very interested in the multitude of opportunities within the field, from book design to advertising. I'm lucky enough to try out many materials and skills, including painting and illustration, through my education at Colorado State University. I'm also experienced with coding and animation, which has helped to expand my creative reach. Even across all of these, I find that there's always a way to add them into graphic design. When starting a project, I strive to fully understand what the end goal of the design is. What should people feel, and what message do I want to convey? Once I fully understand the goal, I try out multiple designs to see which one fits the project best, then I go in and make sure that everything involved is consistent, from the color palette to the logo elements. I trust this process not only for graphic design, but for any creative project that I get to be a part of. More than anything, the work I make needs to be unique and appealing to its audience. I evoke emotions, but also need people to be able to get what they need from my art, even if that differs between each person. I draw inspiration from film and entertainment media, such as animation. I'm fascinated by how many different stories are told in one sitting, and how people read those stories differently. I like to depict movements and stories in my work, while also capturing the overall essence I want to convey. Graphic design, as it is a combination of multiple mediums, allows this sense of freedom and exploration while also being efficient in communicating.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design